On the stability of preferences: Repercussions of entrepreneurship on risk attitudes - Mattias Brachert; Walter Hyll (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The majority of empirical studies make use of the assumption of stable preferences in searching for a relationship between risk attitude and the decision to become and stay an entrepreneur. Yet empirical evidence on this relationship is limited. In this paper, we show that entry into entrepreneurship itself plays a decisive role in shaping risk preferences. We find that becoming self-employed is indeed associated with a relative increase in risk attitudes, an increase that is quantitatively large and significant even after controlling for individual characteristics, different employment status, and duration of entrepreneurship. The findings suggest that studies assuming that risk attitudes are stable over time suffer from reverse causality; risk attitudes do not remain stable over time, and individual preferences change endogenously.
Keywords: D03; D81; M13; 330; Endogenous preferences; Risk attitudes; Entrepreneurship; German Socio-Economic Panel